Environmental Sustainability : Scrutinizing the State of States - Kateja, Alpana; Medatwal, Poorvi (Arthshastra Indian Journal of Economics & Research, 2024)
Purpose : Environmental sustainability has become the most pressing worry for humanity as a result of the race for development’s detrimental impacts on the environment. The current study aimed to assess the major Indian states’ environmental quality. Methodology : The 2019–2021 environmental health status was evaluated in this paper. By using principal component analysis (PCA), four composite indexes have been created. Borda’s rule is utilized to calculate the composite environmental quality score (CEQS) based on rankings of sub-indices. Spearman’s rank correlation has been calculated in order to investigate the relationship between the level of development and environmental sustainability. Findings : Himachal Pradesh and Goa are the only states that have performed consistently well in all sub-indices and thus achieved the top badge in the overall environmental quality category. The states of Assam, Manipur, and Tripura in the Northeast have done a good job of conserving their resources. The four states with the lowest environmental quality were Uttar Pradesh, Gujarat, Maharashtra, and Delhi. According to the report, states with more development are grouped with those that have more environmental damage. Practical Implications : In order to create a sustainable and environmentally friendly future, the research recommended that governmental policies incorporate sustainable practices with the goal of striking a balance between environmental concerns and economic realities. Originality : In contrast to other research, this study looked at disaggregated data and ranked the major Indian states based on how well they performed in terms of environmental sustainability and looked at the relationship between that performance and development level. PCA and cluster analysis are used in this research.